The Let’s Eat Healthy and Move at School program for adolescents in South Korea: Program design, implementation, and evaluation plan using intervention mapping - Jiyoung Park (Korean Academy of Child Health Nursing, 2021)
Purpose This study aimed to systematically develop an obesity prevention program for adolescents to promote healthy eating and physical activity in schools. Methods The development of the Let's Eat Healthy and Move at School program for adolescents followed the six steps of intervention mapping (IM). IM is a widely used protocol for developing systematic and effective interventions based on theories and evidence. Results To better understand the problem and identify the needs of adolescents, interviews were conducted with teachers, school nurses, and students (step 1). In step 2, the desired behaviors and their determinants were established and combined into a matrix comprising 16 change objectives. In step 3, theoretical methods such as persuasive communication and consciousness-raising were chosen. The program was segmented into three educational activity sessions in step 4. In step 5, an implementation manual was developed for program instructors to ensure effective and accurate implementation. Finally, practices for evaluating the program's effectiveness and procedures were designed in step 6. Conclusion The Let’s Eat Healthy and Move at School program will provide adolescents with guidelines to promote healthy living and prevent obesity in everyday life using strategies for sustainable adolescent obesity prevention and management.